North African Apologetics - Williams, D. H. (Defending and Defining the Faith: An Introduction to Early Christian Apologetic Literature, 2020)
This chapter considers the work of Arnobius, who presents the most mysteries of all the figures discussed in this book, both in terms of himself and in terms of what he was precisely attempting to achieve with his only known work, Against the Pagans (Adversus nations). There is almost no externally verifiable information on Arnobius except his authorship of this work, penned about fifty years after Cyprian’s death, likely during or just after the “great persecution” that the emperor Diocletian inaugurated from 303 until it was unexpectedly halted in 311 by Galerius—one week before his death. Against the Pagans provides a window into the intellectual debate of the time, through its engagement with the religious and philosophical standpoints that underpinned the outburst of anti-Christian feeling of the Diocletianic persecution. Just as Lactantius’s Divine Institutes and Eusebius’s Preparation of the Gospel will do, so Arnobius is rebutting the pagan attempts to justify the gods’ perceived anger toward Christianity. This chapter is also concerned with Lactantius
paid